Endothelium-dependent mechanisms of nephroprotective effect of renin-angiotensin system modulators in patients with essential hypertension - Kulynych, R. L.; Glavatskiy, O. M.; Sychov, R. O.; Kulynych, O. V.; Svystun, S. I. (Journal of Education, Health and Sport, 2020)
Introduction. It has been shown that essential hypertension (EH) is one of the main causes of end-stage renal failure in 10-30% of patients on programmed hemodialysis. At the same time, according to some clinical studies, it was shown that the most widely used drugs (diuretics, beta-blockers, calcium channel antagonists, etc.) effectively reduce high blood pressure (BP), are able to prevent the development of myocardial infarction and cerebral catastrophes, however, do not have a sufficient nephroprotective effect. The aim of the study is to identify the nephroprotective efficacy of angiotensin-converting enzyme inhibitors and angiotensin II receptor antagonists in patients with EH. Materials and methods of research. To achieve this goal, 40 patients with stage I-II EH with a level of I-III degree of arterial hypertension at the age of 34 to 63 years (mean age 45.8±1.14 years) were examined, without adequate systematic antihypertensive therapy, in which, as a result of a complex clinical-anamnestic and instrumental-laboratory research, there were no data which can indicate on the presence of manifest hypertensive nephropathy and other clinically significant expressed signs of chronic kidney diseases. Research results. Evaluation of the obtained results showed that patients of both groups had a significant antihypertensive effect: the decrease in systolic BP and diastolic BP at the end of the course of therapy in patients of group 1 was 18.24% and 15.67%, in the group 2 was 17.32% and 15.44 %, respectively. The dynamics of urinary albumin excretion at the end of the course of therapy was also found to be reliable in comparison with the primary data: in the treatment with enalapril the level of albuminuria decreased by 25.13%, excretion of β2-microglobulin decreased by 18.82%. In group 2, the decrease in these indicators was 16.34% and 17.46%, respectively (p <0.05). It should be noted a statistically significant decrease in glomerular permeability index, an indirect marker of intraglomerular hypertension: for patients in group 1 by 19.14%, for patients in group 2 by 14.12%, respectively. Evaluation of the effectiveness of the treatment on the functional state of the kidneys in the examined patients with EH showed that in 19 patients (82.61%) of the 1st group and in 15 patients (68.18%) of the 2nd group, therapy was regarded as effective. Conclusions. Therapy with enalapril and irbesartan has a significant antihypertensive and nephroprotective effect. Evaluation of indicators characterizing the functional state of the kidneys in patients with essential hypertension during therapy indicates that enalapril has a more pronounced nephroprotective effect in comparison with irbesartan. The effectiveness and rationality of nephroprotective therapy is largely determined by the positive dynamics in the reserve capacity of the kidneys and in the restoration of the functioning of the vascular endothelium.